ANALISA Z SCORE SEBAGAI PREDIKTOR KEBANGKRUTAN PERUSAHAAN DAN PROFITABILITAS PADA INDUSTRI JASA SUB SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA - Mariyam Zanariyah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
ABSTRACTThis study aims to determine how to predict corporate bankruptcy using a Z Score and to determine whether partially or simultaneously variables Working Capital / Total Assets, Retained Earnings / Total Assets, Earnings Before Interest and Taxes / Total Assets, Stock Market Value / Total Payable and Sales / Total Assets significant effect on profitability (return on equity). This information is useful for management and creditors in making decisions.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The data used in this study is the Financial Statements period ended 31 December 2007- December 31, 2012 Transportation Services Industry Sub-Sector in Indonesia Stock Exchange with a population of 25 companies and a sample obtained by using purposive sampling technique which amounts to 9 companies. Model analysis using the equation Z Score by category value Z score: Z <1.8 Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â (: Bankrupt), 1.8 <Z <2.99 (: Grey) and Z> 2.99 (: Not Bankrupt) and multiple regression using SPSS 20.0.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The results showed that: 1). On the average of the years 2007-2012 the value of Z Score of -1.2 categorized Bankrupt. However, if there are several companies partially as: PT Tanah Laut Tbk from years 2009-2011 and PT Entris Multi Pratama Tbk in 2012 categorized Not Bankrupt. 2). Partially Working Capital / Total AssetsÃ‚Â variables, Earnings Before Interest and Tax / Total AssetsÃ‚Â and the Stock Market Value / Total DebtÃ‚Â significantly affect the profitability (return on equity). While Retained Earnings / Total Assets variable and Sales / Total AssetsÃ‚Â does not significantly affect the profitability of the Company, so that the first hypothesis is not proven. 3). Simultaneously all independent variables studied are significantly affect the profitability of the Company, meaning that the second hypothesis is proven. 4). Stock Market Value / Total DebtÃ‚Â variable is a variable that has dominant influence on the profitability of the Company, not Working Capital / Total Assets variables as previously thought, meaning that the third hypothesis is not proven. 5). The coefficient of determination obtained amounted to 59.40%, meaning that there are other variables that affect the profitability of the Company amounted to 40.60% more that have not been studied.Ã‚Â Key Word : Z Score, Profitability,Indonesia Stock Exchange.